Malignant Ischemic Stroke in a Young Female: A Rare Primary Manifestation of Takayasu Arteritis - Bhupendra Shah; Roshan Chhetri (Case Reports in Neurological Medicine)
Takayasu arteritis is a rare chronic progressive granulomatous necrotizing large vessel panvasculitis mainly involving aorta and its main branches. It commonly affects the female in second to third decades. Common clinical features of Takayasu arteritis are hypertension, claudication, dizziness, headache, or fever. Takayasu arteritis is diagnosed with clinical history of claudication, absent pulse, discordant blood pressure, bruit over aorta, and typical angiographic findings. Stroke as a primary manifestation of Takayasu arteritis is rarely reported in the medical literatures. We are reporting a 16-year-old female who had malignant ischemic stroke as a first manifestation of Takayasu arteritis.